2012
DOI: 10.1016/j.rser.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability at home: Policy measures for energy-efficient appliances

Abstract: Residential energy consumption is now an important component of total energy consumption and its related emissions. In addition,this consumption has significant potential for growth in both developed and developing countries, as average incomes increase, and domestic appliance numbers rise. Reduction in this energy use may be achieved both through conservation measures, and through increased efficiency in its use. This paper focuses on energy efficiency in appliances-those many devices through which household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…According to a study of 1,300 households conducted in 12 European countries 1 by De Almeida et al [47], standby use corresponds to around 11% of the total energy consumption in the residential sector (not including space and water heating), equivalent to approximately 40W per household. This is consistent with studies conducted in Germany, Holland, the United States, and Australia which revealed that roughly 10% of domestic electricity use in these countries is due to standby power [20,46].…”
Section: Historical Review Of the Uk's Household Entertainment Appliasupporting
confidence: 90%
See 1 more Smart Citation
“…According to a study of 1,300 households conducted in 12 European countries 1 by De Almeida et al [47], standby use corresponds to around 11% of the total energy consumption in the residential sector (not including space and water heating), equivalent to approximately 40W per household. This is consistent with studies conducted in Germany, Holland, the United States, and Australia which revealed that roughly 10% of domestic electricity use in these countries is due to standby power [20,46].…”
Section: Historical Review Of the Uk's Household Entertainment Appliasupporting
confidence: 90%
“…The corresponding residential electricity consumption per person ranges from 1.6 MWh/capita/year in the EU27 to 4.5 MWh/capita/year in the US, compared to the global average of 2.5 MWh/capita/year [20]. Electrical appliances and devices impact on household electricity consumption through the electric power that they consume, based on the amount of time each appliance is in use and the consumption mode.…”
Section: Background: Classifications and Most Common Patternsmentioning
confidence: 99%
“…This rapid rise was observed because appliance ownership has increased in both the developed and developing countries. Furthermore, considering the relationship between income and appliance ownership, it can be predicted that increases in GDP per capita in most developing countries will lead to further major growth in appliance utilization [11,20].…”
Section: Electricitymentioning
confidence: 99%
“…1 demonstrates the percentage of total consumption that is residential in different regions of the world, which fluctuates from an average of 20% in the developed countries to more than 35% in the developing countries [10]. Residential energy demand is prominent both for its present size and potential growth [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was more common to treat energy consumers as individuals than as households. Six articles treated individuals as energy consumers [40][41][42][43][44][45], while five articles treated energy users as individuals [46][47][48][49][50].…”
Section: Household or Household's Members As Targets Of Information?mentioning
confidence: 99%